Crenças verdadeiras e justificação: a aporia platônica e suas novas versões - Fanticelli, Lutecildo (Universidade do Vale do Rio dos Sinos, 2013)
In the Plato’s Theaetetus the aporia is one specie of empty philosophical, because it postpones the most admirable definition of knowledge, i. e, the definition as justified true belief. An aporetic Dialogue is a Dialogue without the answer that’s been searched and this is the case of the Theaetetus. Socrates claims some urgent necessities to does not maintain the definition. However, a careful investigation reveals some insufficiency in those counterarguments. Some of them, besides insufficient, are exposed of one summarized way. In this way, it had become necessary an investigation to attain the validity about those refutations, which ended in the Dialogue’s aporia. But despite that, the problem of Theaetetus is, in fact, very difficult. There is, for example, an enormous tendency of amalgamation among the concept of true belief and the concept of logos. The simple definition of logos is an extenuated work. In the 20th century, the concise text of Gettier gave rise to the same discussion that Theaetetus. In a few words, it corroborated with the platonic refutation and attracted much attention to itself. This thesis discusses more specifically about Plato’s Theaetetus, which is the Dialogue delimited and fundamental text to investigation. What is inquired is primarily the legitimacy of the platonic counterarguments, which one of Gettier comes in less proportion. If they are not consistent, then we are yet warranted to carry on defining knowledge as justified true belief. After Theaetetus’ publishment a large amount of epistemologies have been produced and many answers to the problem of Gettier are also, in a certain way, answers to Theaetetus. The epistemic justification that is so discussed nowadays is seems to be the same justificational logos debated in the Theaetetus. The contemporary philosophers search for the logos that the dialoguers probably did not attain. This thesis displays how neither Plato nor Gettier made to refute the tripartite definition. Costa’s suggestion about the necessity of assuming a perspectivist condition and a current condition is, indeed, plausible as the resolution of Gettier’s counterexample. Neoclassic foundationalism of Bonjour is also one alternative too plausible. Indeed, his presupposition of beliefs without necessity of justification let us free of the ancient worry of infinite regress. According to the author, is necessary to presuppose one notion of non apperceptive consciousness, whereby occur the relation between the sensorial experience and the fundamental belief. In part, if the Theaetetus, is adequately investigated, it answers some questions, because, at the end, we can see the insufficiency of the counterarguments. In other, the contemporary doxastology relieves the problem with new proposals. In short, one careful investigation of own Theaetetus allied to one clear and elucidative foundationalism answer, of plausible way, the problem here exposed. However, since that the Theaetetus is the main text to investigation, this thesis stress it more abundantly.
Keywords: Conhecimento; Crença; Refutação; Coerção; Knowledge; Belief; Disproof; Coercion; Justificational logos; Logos justificacional; ACCNPQ::Ciências Humanas::Filosofia